Size and contrast increase the divertive effect of eyespots. (24th October 2018) - Kjernsmo, Karin; Grönholm, Miranda; Merilaita, Sami
Abstract : Eyespots can protect prey by diverting predator attacks, but what makes an eyespot divertive? Using 3-spined sticklebacks and artificial prey, we studied how manipulation of 2 visual properties of the eyespot, size, and internal contrast, while keeping prey conspicuousness constant, influence where attacking fish direct their strikes. An increase in size and internal contrast, independently of each other, significantly increased the divertive effect of eyespots. This increases our knowledge about the selection pressures that shape eyespots. Abstract: Recent studies have shown that some eyespots of prey divert the strikes of predators, increasing the likelihood of prey escape. However, little is known about what makes eyespots effective divertive (deflective) prey marks. The size of eyespots varies much both between and even within taxa. Yet, whether size is important for the divertive function of eyespots is unknown. Furthermore, eyespots have often been described as highly contrasting, but the effects of contrast on the divertive function of eyespots has never been tested experimentally. Using artificial prey and the three-spined stickleback ( Gasterosteus aculeatus ) as a model for predator cognition and behavior, we tested the importance of size as well as internal contrast for the divertive effect of eyespots. We independently increased the internal contrast and size of eyespots and found that both increased the divertive effect. The effect of size was significant over all 4 subsequent prey presentations, whereas the effect of contrast decreased after the initial presentations. These results suggest that the size and contrast of divertive marks are probably shaped by selection imposed by predation. We also discuss the involvement of predation in the seasonal and ontogenic plasticity of eyespots found in some taxa.